1990
DOI: 10.1111/j.1346-8138.1990.tb03712.x
|View full text |Cite
|
Sign up to set email alerts
|

Poikiloderma‐like Lesions on the Neck in Atopic Dermatitis: A Histopathological Study

Abstract: Reticulate pigmentation with or without skin atrophy, depigmentation and telangiectasia is frequently encountered on the neck of severe cases of adult type atopic dermatitis. These skin changes were graded clinically into 3 stages. Based on histological features, hyperplasia of the sebaceous gland, dilated tortuous capillaries, and mild degeneration of elastic fibers were noted in stage I lesions. Lesions of both stages II and III contained increased melanin in the basal cell layer with incontinence of pigment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…They become more evident during puberty and adulthood and are more pronounced in males compared to females [21], which may explain the male predominance and the characteristic age of onset of the pigmentation in adolescence that was found in this study. Interestingly, Mukai et al [5] reported histological evidence of sebaceous hyperplasia in 13 of the 23 AD patients with ‘poikiloderma-like lesions on the neck', which supports this association, although this finding was not evident in any of our biopsy specimens. Moreover, ‘juxta-clavicular' or neck pigmentation is misleading, as similar pigmentary changes can also affect other sites such as the axillae and cubital fossae, a finding which has been reported by others [4,12,17,18].…”
Section: Discussionmentioning
confidence: 31%
See 2 more Smart Citations
“…They become more evident during puberty and adulthood and are more pronounced in males compared to females [21], which may explain the male predominance and the characteristic age of onset of the pigmentation in adolescence that was found in this study. Interestingly, Mukai et al [5] reported histological evidence of sebaceous hyperplasia in 13 of the 23 AD patients with ‘poikiloderma-like lesions on the neck', which supports this association, although this finding was not evident in any of our biopsy specimens. Moreover, ‘juxta-clavicular' or neck pigmentation is misleading, as similar pigmentary changes can also affect other sites such as the axillae and cubital fossae, a finding which has been reported by others [4,12,17,18].…”
Section: Discussionmentioning
confidence: 31%
“…A previous study from Japan reported a much higher prevalence of 35.5% in an adult AD cohort [5]. In contrast, a study by Trautmann et al [12] found a lower prevalence of 5.9% in a Caucasian cohort.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In the past decade, new types of skin manifestations such as persistent erythema on the face and glucocorticoid (GC)‐resistant skin inflammatory response, have been recognized in patients with atopic dermatitis (AD), especially in Japan [1–3] and the USA [4]. Such manifestations are frequently observed in adult patients with AD after the long‐term use of topical GC, and have been called adult type‐AD.…”
Section: Introductionmentioning
confidence: 99%
“…Such manifestations are frequently observed in adult patients with AD after the long‐term use of topical GC, and have been called adult type‐AD. It is speculated that these skin manifestations are induced by either a withdrawal effect of topical GC or a direct and/or indirect effect of topical GC [1–3]. To clarify whether topical GC modulates cutaneous inflammatory reactions, we previously found topical GC to augment both the contact hypersensitivity (CHS) reaction and irritant reactions in mice [5]; however, the mechanism of this enhanced cutaneous inflammatory response induced by GC still remains unclear.…”
Section: Introductionmentioning
confidence: 99%